Books in motion : connecting preschoolers with books through art, games, movement, music, playacting, and props - Dietzel-Glair, Julie, 1976- (Neal-Schuman, an imprint of the American Library Association, 2013)
"Books in Motion: Connecting Preschoolers with Books through Art, Games, Movement, Music, Playacting, and Props shows you exactly how to use children?s books to engage preschool-age children through movement. With this amazing new resource, your next storytime will have children standing up tall, balancing as they pretend to walk across a bridge, and flying around the room like an airplane"--The publisher.